An urgent urban design challenge: time, sustainable mobility, and the humanization of collective space - Bandeira, Miguel Sopas de Melo (2021)
This chapter is intended as a reflection on three concepts that are considered interdependent: time, sustainable mobility, and the humanization of the collective space. The identity and position of each city in relation to the level of sustainable urban mobility achieved and the appetite for the humanization of its collective spaces are determined by its location in time, with regard to its degree of maturity in the implementation of these concepts. It is therefore crucial to define them and to determine mechanisms for critical evaluation and monitoring in time that contribute to the definition of standards and a theory that helps to accelerate the processes of changing behaviour and paradigms in terms of mobility and urban design.